Multi-layer state of health balancing control for a battery-based energy storage system to extend cycle life based on active equalization circuits - Li, Xiaohang; Yin, Xin; Tian, Zhongbei; Jiang, Xinyu; Jiang, Lin; Smith, Jeremy (Frontiers in Energy Research, 2022)
State of health (SoH) imbalance causes capacity waste and cycle life reduction of the battery-based energy storage systems (BESS), which demands SoH balancing control of the parallel-connected packs and the series-connected cells of the BESS. This study proposed a multi-layer SoH balancing control to extend the cycle life of the BESS. For the series-connected battery cells, active equalization circuits based on the fly-back converter are used to exchange energy between cells and control the depth of discharge (DoD) of cells to achieve the SoH balance. For the parallel-connected packs, SoH is equalized by distributing the output power based on the SoH balancing principle and the minimum power distribution constraints of packs caused by the bidirectional balancing current among the series-connected cells are considered. Because the proposed method achieves the SoH balancing by utilizing the active equalization circuits to transfer the energy between the cells with different SoH, it can achieve higher capacity and energy utilization efficiency and lower heat release compared with the passive equalization typology that dissipates the energy. The effectiveness of the proposed method is verified by a case study based on a 3-packs-15-cells BESS. Simulation results show that this method can prolong the cycle life of BESS by about 52.9% compared with the active SoC balancing method using the same fly-back converter and 18.3% with a passive multi-layer SoH balancing method, respectively.